2006
DOI: 10.1111/j.1365-2850.2006.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinician perceptions of personal safety and confidence to manage inpatient aggression in a forensic psychiatric setting

Abstract: Inpatient mental health clinicians need to feel safe in the workplace. They also require confidence in their ability to work with aggressive patients, allowing the provision of therapeutic care while protecting themselves and other patients from psychological and physical harm. The authors initiated this study with the predetermined belief that a comprehensive and integrated organizational approach to inpatient aggression was required to support clinicians and that this approach increased confidence and staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 39 publications
2
73
0
1
Order By: Relevance
“…Moreover, the relative isolation of co-acting group members (compared to those with real team membership who share a common goal with their teammates) means that they can more easily be subject to abuse by patients, their relatives and other members of the public (Hayes & Bonnet, 2010). Indeed, Martin and Daffern (2006) found that a team approach was fundamental to manage patient aggression and maintain perceptions of personal safety amongst mental health clinicians. Further, poor team communication, an unsafe team approach, and a lack of team support were all factors that reduced staff confidence in managing aggressive patients.…”
Section: Consequences Of Real Team and Co-acting Group Membershipmentioning
confidence: 99%
“…Moreover, the relative isolation of co-acting group members (compared to those with real team membership who share a common goal with their teammates) means that they can more easily be subject to abuse by patients, their relatives and other members of the public (Hayes & Bonnet, 2010). Indeed, Martin and Daffern (2006) found that a team approach was fundamental to manage patient aggression and maintain perceptions of personal safety amongst mental health clinicians. Further, poor team communication, an unsafe team approach, and a lack of team support were all factors that reduced staff confidence in managing aggressive patients.…”
Section: Consequences Of Real Team and Co-acting Group Membershipmentioning
confidence: 99%
“…In the research literature, increasing attention is devoted to staff management of and attitudes toward inpatient aggression (Björkdahl, Olsson, & Palmstierna, 2006;Bowers et al, 2006;Duxbury, 2005;Martin & Daffern, 2006;Meehan, McIntosh, & Bergen, 2006;Needham et al, 2005). Improvement of the interaction between staff and patients, for example, by collaborating on relapse prevention plans, may lead to a reduction of rates of inpatient violence (Duxbury & Whittington, 2005;Fluttert et al, 2008;Kettles, 2004;Meehan et al, 2006).…”
mentioning
confidence: 98%
“…T HE OCCURRENCE OF severe aggressive incidents on acute psychiatric wards is a serious problem and can have a great impact on staff; they can trigger feelings of shock, fear, or anger and are often followed by rumination, guilt, or anxiety (Bowers, Brennan, Flood, Lipang, and Olapado, 2006;Camerino, Estryn-Behar, Conway, Heijden van der, & Hasselhorn, 2007;Jonker, Goosens, Steenhuis, & Oud, 2008;Martin & Daffern, 2006;Mason, King, & Dulson, 2009;Needham, Alberhalden, Halfens, Fischer, & Dassen, 2005). Patients also suffer from the consequences of their aggressive behavior; it is likely that these kinds of behaviors cause conflicts with staff, possibly resulting in coercive measures (Meehan et al, 2006;Paterson & Duxbury, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 The issues of sex, experience, and perceptions are more fully reviewed elsewhere. 10 While some patients may be at increased risk for violence, the awareness of this possibility is typically proportionally heightened in these facilities.…”
Section: Safety Concernsmentioning
confidence: 99%